2011
DOI: 10.15669/pnst.2.543
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of Turbulent Channel Flow with Deformed Bubbles

Abstract: In this study, the direct numerical simulation of a fully-developed turbulent channel flow with deformed bubbles were conducted by means of the refined MARS method, turbulent Reynolds number 150, and Bubble Reynolds number 120. As the results, large-scale wake motions were observed round the bubbles. At the bubble located region, mean velocity was degreased and turbulent intensities and Reynolds shear stress were increased by the effects of the large-scale wake motions round bubbles. On the other hands, near w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the same configuration, Bolotnov et al (2011) investigated a swarm of nearly spherical bubbles and observed that bubbles tend to rise in the wall region and to increase the production of turbulence. Yamamoto and Kunugi (2011) analyzed the behavior of four bubbles at somewhat larger bubble Reynolds number, around 120. They noted that two of the bubbles stayed mainly in the center region and that one bubble rose in the near-wall region, possibly captured by the low-pressure zone of high-speed streaks, and no information was given on the fourth bubble.…”
Section: Introductionmentioning
confidence: 99%
“…In the same configuration, Bolotnov et al (2011) investigated a swarm of nearly spherical bubbles and observed that bubbles tend to rise in the wall region and to increase the production of turbulence. Yamamoto and Kunugi (2011) analyzed the behavior of four bubbles at somewhat larger bubble Reynolds number, around 120. They noted that two of the bubbles stayed mainly in the center region and that one bubble rose in the near-wall region, possibly captured by the low-pressure zone of high-speed streaks, and no information was given on the fourth bubble.…”
Section: Introductionmentioning
confidence: 99%